2011
DOI: 10.1152/physrev.00003.2008
|View full text |Cite
|
Sign up to set email alerts
|

Zonulin and Its Regulation of Intestinal Barrier Function: The Biological Door to Inflammation, Autoimmunity, and Cancer

Abstract: The primary functions of the gastrointestinal tract have traditionally been perceived to be limited to the digestion and absorption of nutrients and to electrolytes and water homeostasis. A more attentive analysis of the anatomic and functional arrangement of the gastrointestinal tract, however, suggests that another extremely important function of this organ is its ability to regulate the trafficking of macromolecules between the environment and the host through a barrier mechanism. Together with the gut-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
633
1
35

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 765 publications
(724 citation statements)
references
References 174 publications
13
633
1
35
Order By: Relevance
“…Zonulin, which can induce tight junction disassembly and increase intestinal permeability, is upregulated in T1D, and gliadin induces zonulin upregulation in the intestinal cell line Caco2 [37]. This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Zonulin, which can induce tight junction disassembly and increase intestinal permeability, is upregulated in T1D, and gliadin induces zonulin upregulation in the intestinal cell line Caco2 [37]. This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regulation of the exchange of molecules between the environment and the host through the intestinal barrier influences the equilibrium between tolerance and immunity to self and non-self-antigens (Fasano, 2011). From a structural perspective these functions are preserved by a number of features including a mucus layer and a monolayer of epithelial cells interconnected by tight junctions.…”
Section: Microbes Gut Barrier and Inflammationmentioning
confidence: 99%
“…Is it a cause, consequence or coevolutional phenomenon? [10,[27][28][29]. Data is accumulating that intestinal luminal environmental factors might perturbate the regulatory mechanisms of the tight junction, resulting in a leaky gut thus breaking equilibrium between tolerance and immunity to nonself-antigens.…”
Section: The Leaky Gut and Autoimmunitymentioning
confidence: 99%
“…Nutrients, toxins, allergens, carcinogens, intestinal infections, dysbiotic bacteria, drugs and stress and the recently described industrial processed food additives, can breach the tight junction integrity [3,4,[7][8][9][10]12,13,[15][16][17][18]23,24,28,29]. In fact, TJ dysfunction seems to be a primary defect in AD [28][29][30]. Intestinal permeability is increased in many AD: Ulcerative colitis, Crohn's disease, CD, inflammatory joint disease, ankylosing spondylitis, juvenile onset arthritis, psoriatic arthritis, type 1 diabetes mellitus and primary biliary cirrhosis.…”
Section: The Leaky Gut and Autoimmunitymentioning
confidence: 99%